2009
DOI: 10.1111/j.1439-0507.2008.01673.x
|View full text |Cite
|
Sign up to set email alerts
|

The protein secretory pathway of Candida albicans

Abstract: Virulence of the opportunistic pathogen, Candida albicans, relies on an assemblage of attributes. These include the secretion of hydrolytic enzymes, cell surface adhesins, morphological transition between yeast and hyphae, phenotypic switching and biofilm formation. These diverse features are united by their dependence on the protein secretory apparatus for expression. Although the secretory apparatus of C. albicans has been studied limitedly, it appears to conform to the well-conserved eukaryotic system of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 118 publications
(245 reference statements)
0
27
2
Order By: Relevance
“…The exact C. albicans factors triggering macrophage pyroptosis are currently unknown, yet recent investigations revealed that the level of hyphal formation and exposure of specific moieties on the fungal cell wall play a role in this process (14)(15)(16). Since neutral pH is a potent morphogenetic signal in C. albicans and cell wall composition depends on the available carbon sources (25,26), we explored if the effects of the stp2Δ and ahr1Δ mutations on IL-1␤ release were related to the inability of the mutants to prevent phagosomal acidification. For this purpose, we pretreated the J774A.1 macrophages with the vATPase inhibitor BafA to generate neutral phagosomes, followed by addition of C. albicans strains.…”
Section: Resultsmentioning
confidence: 99%
“…The exact C. albicans factors triggering macrophage pyroptosis are currently unknown, yet recent investigations revealed that the level of hyphal formation and exposure of specific moieties on the fungal cell wall play a role in this process (14)(15)(16). Since neutral pH is a potent morphogenetic signal in C. albicans and cell wall composition depends on the available carbon sources (25,26), we explored if the effects of the stp2Δ and ahr1Δ mutations on IL-1␤ release were related to the inability of the mutants to prevent phagosomal acidification. For this purpose, we pretreated the J774A.1 macrophages with the vATPase inhibitor BafA to generate neutral phagosomes, followed by addition of C. albicans strains.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that the transition from the a virulent form of C. albicans to a pathogenic one requires the secretion of proteins to the cell surface and surrounding matrix, few studies have investigated the basic biology of the early secretory pathway in C. albicans , namely the translocation of secretory proteins into the endoplasmic reticulum (ER; reviewed in Fonzi 2009). A few C. albicans proteins presumed to play roles in the early secretory pathway have been shown to function similarly to their Saccharomyces cerevisiae orthologs, such as SEC65 (Regnacq et al 1998) and SPC3 , an ER resident protein involved in N-terminal signal sequence cleavage (De la Rosa et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…These secreted proteases are required for pathogenicity, as they take part in fungal attachment, invasion, and subsequent tissue damage (4)(5)(6)(7). These factors are secreted by mechanisms that include traditional signal peptide-based secretion using systems homologous to those in the model yeast Saccharomyces cerevisiae as well as nontraditional secretion (8,9).…”
mentioning
confidence: 99%